EVALUASI TUNDAAN PADA SIMPANG EMPAT TAK BERSINYAL DI KOTA MATARAM (STUDI KASUS : SIMPANG JALAN PEJANGGIK DAN SIMPANG JALAN CATURWARGA) - HASYIM, HASYIM; ROHANI, ROHANI (Universitas Mahasaraswati K. Mataram, 2023)
Pejanggik intersection and Caturwarga intersection are unsignalized intersections in Mataram City. Both intersections have the same characteristics, namely they both have four arms. The location of the two intersections close together causes frequent traffic delays. For this reason, research is needed to optimize the performance of these two unsignalized intersections.The method used to analyze the two intersections is the Indonesian Road Capacity Manual (1997). The data used is primary and secondary data, such as traffic volume, capacity, degree of saturation, delays and queuing opportunities. Results of performance analysis of the Jalan Pejanggik intersection in existing conditions DS = 1.086, delay = 24.2 seconds/pcu, and queuing opportunity = 47.6%. Performance of the Caturwarga Road Intersection in existing conditions DS = 0.97, delay = 18.1 seconds/pcu and queuing opportunity = 38.54%. To improve unsignalized intersections, several alternatives are provided. The first alternative is Jalan Pejanggik Intersection DS = 1.00. delay = 19 seconds/smp and chance of queuing = 40.20%, Jalan Caturwarga DS intersection = 0.95. delay = 17 seconds/smp and chance of queuing = 36.92%. Second alternative Pejanggik Road Intersection DS = 0.97. delay = 18 seconds/smp and chance of queuing = 38.44%, Jalan Caturwarga DS intersection = 0.91. delay = 15.9 seconds/smp and chance of queuing = 33.7%